Морфологічні особливості плодів і насіння видів роду Acacia (Tourn.) L. (родина Leguminosae = Papilionaceae = Fabaceae). Повідомлення 2 - Szikura, J.J.; Szikura, A.J. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
81 species of genus Acacia (Tourn.) L. of different botanical-geographical descendance were studied. Morphological features of these species fruits and seeds are presented.